KONSUMSI KEDELAI, KURMA, DAN DAUN KATUK UNTUK MENINGKATKAN PRODUKSI ASI PADA IBU MENYUSUI - Handayani Handayani; Susanti Pratamaningtyas; Aida Amalia Nur Ramadhian; Isnu Kurnia Nugrahaeni (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2022)
Low production of breast milk is one of the matters of breastfeeding. Some breastfeeding mothers complain that their milk production has not come out. Whereas, exclusive breastfeeding can protect babies from dangerous diseases. The purpose of this study was to analyze the benefits of soybeans, dates, and katuk leaves to increase breast milk production in breastfeeding mothers. This research was a systematic review review based on the Reporting Item Options for Systematic Review and Meta-Analysis Protocol (PRISMA Protocol). Screening was carried out on publications (2014-2019) from electronic data sources, namely PubMed, Google Sholar and Elsevier. Furthermore, selecting journals based on the criteria and obtained as many as 7 journals. The result of this study was most studies prove that soybeans, dates, and katuk leaves can be consumed by breastfeeding mothers and provide benefits for fulfilling nutrition for breastfeeding mothers.Consumption of soybeans, dates, and katuk leaves can be applied by health practitioners to intervene in breastfeeding mothers to increase milk production.